Serum proteomic pattern in female stress urinary incontinence. Issue 8 (6th February 2018) - Koch, Marianne; Umek, Wolfgang; Hanzal, Engelbert; Mohr, Thomas; Seyfert, Sonja; Koelbl, Heinz; Mitulović, Goran
Abstract: The pathophysiology of Stress Urinary Incontinence (SUI) is poorly understood. The aim of this study was to identify the serum proteomic profile in patients with SUI and to replicate findings from a preceding study in which a significant difference in the urinary proteome was identified. Serum samples were collected from 38 patients (19 SUI; 19 matched, continent controls). Sample preparation included serum albumin depletion, in‐solution enzymatic digestion of proteins applying a combination of Gluc‐C and trypsin and peptide separation using nano High Performance Liquid Chromatography. Label‐free quantitation of peptides and proteins was performed after triplicate measurements using quadrupole time‐of‐flight mass spectrometry. Peptide identification was achieved by searching the Human SwissProt Database using Mascot and X!Tandem. Main outcome measure was the relative abundance of each detected protein in serum. Of 7012 identified proteins, 33 proteins were induced (detected in SUI, not in controls) and five proteins were depleted (detected in controls, not in SUI). All depleted proteins play a role in immune/DNA damage response. Induced proteins are involved in inflammatory response, response to cellular stress, coagulation and cytoskeleton stability/ motility. Plasma serine protease inhibitor (SERPINA5) was found induced and previously also showed a higher abundance in urine samples of SUI patients. Data are available via ProteomeXchange with identifier PXD008553.